FENOMENA EKSPLOITASI LINGKUNGANDALAM CERPEN KORAN MINGGU INDONESIA PENDEKATAN EKOKRITIK - Juanda Juanda (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2018)
Environmental damage on earth is at a critical level. Climate change, disaster, pollution, and animal hunting continue to occur without realizing that humans are part of their lives. The purpose of this research, first, is to explore the form of imagination of Indonesian story writer with the theme of environment. Second, to analyze the ecocritical element that is reflected by the author through short story weekly newspaper in Indonesia. This study used descriptive qualitative method. The approach this research used is Garrard's ecocritical approach. The data source consists of three short stories, namely,